Negative Interest Rate Policies-Initial Experiences and Assessments. (Policy Papers; Policy Paper ;, 2017)
The depth of the crisis and the weakness of the ensuing recovery led to new ways to implement monetary policy. At the onset of the crisis, central banks in several advanced economies quickly moved policy rates to zero and initiated large-scale asset purchases. In more recent years, with inflation still below target and limited support from fiscal policy, several central banks lowered their policy rates below the previous zero lower bound, embarking on so-called negative interest rate policies (NIRPs). This paper explores the implications of NIRPs for monetary policy transmission and banks' behavior. It considers potential differences between interest rate cuts in positive versus negative territory on deposit and lending rates, as well as banks' interest rate margins and profitability, and market functioning. The paper focuses on the bank transmission channel, where differences between positive and negative policy rates could arise. Finally, the paper reviews cross-country experiences through case studies.